(GTG)(5)-PCR fingerprinting of lactobacilli isolated from cervix of healthy women - Švec, Pavel; Sedláček, Ivo; Chrápavá, Marika; Vandamme, P (Folia microbiologica, 2011)
A group of lactobacilli isolated from the cervix of 31 healthy women was characterized by (GTG)(5)-polymerase chain reaction (PCR) fingerprinting in order to evaluate this method for identification of vaginal lactobacilli. Obtained fingerprints were compared with profiles available in an in-house database of the CCM bacteria collection covering type and reference strains of multiple lactic acid bacteria including lactobacilli. Selected strains representing individual clusters were further identified by pheS gene sequencing. In total, six lactobacillus species were found among lactobacilli isolated from the cervix of healthy women. The (GTG)(5)-PCR method identified Lactobacillus gasseri (11 strains), Lactobacillus fermentum (one), and some of the Lactobacillus jensenii strains (eight out of 11), but failed to identify the remaining strains, including the Lactobacillus crispatus (18), Lactobacillus mucosae (one), and Lactobacillus vaginalis (one) species. L. jensenii strains were distributed over two fingerprint clusters. The majority of samples was dominated by one (GTG)(5)-PCR type. The rep-PCR fingerprinting using the (GTG)(5) primer allowed straightforward identification of many, but not all, isolates. This method has been shown to be a useful tool for fast screening and grouping of vaginal lactobacilli, but its combination with another identification method is needed to obtain reliable identification results. In addition, Lactobacillus acidophilus was not shown to be the most common inhabitant of the female genital tract as generally assumed.
Keywords: dospělí; Female; Lactobacillus; polymerázová řetězová reakce; Adult; Polymerase Chain Reaction; mladý dospělý; ženské pohlaví; DNA bakterií; DNA Fingerprinting; cervix uteri; Adolescent; DNA, Bacterial; lidé; DNA primery; DNA fingerprinting; Phylogeny; Young Adult; Bacterial Typing Techniques; techniky typizace bakterií; DNA Primers; fylogeneze; Cervix Uteri; mladiství; Humans